Enhancement of BDNF Concentration and Restoration of the Hypothalamic-Pituitary-Adrenal Axis Accompany Reduced Depressive-Like Behaviour in Stressed Ovariectomised Rats Treated with Either Tualang Honey or Estrogen - Al-Rahbi, Badriya; Zakaria, Rahimah; Othman, Zahiruddin; Hassan, Asma’; Ahmad, Asma Hayati (Hindawi Publishing Corporation, 2014)
A possible interaction between glucocorticoids and estrogen-induced increases in brain-derived-neurotrophic factor (BDNF) expression in enhancing depressive-like behaviour has been documented. Here we evaluated the effects of Tualang honey, a phytoestrogen, and 17